The Great Recession and the changing intergenerational distribution of economic stress across income classes in Ireland: A comparative perspective - Whelan, C; Nolan, B; Maître, B (SAGE Publications, 2016)
In this paper we seek to bridge the gap between recent analysis relating to the distributional consequences of the Great Recession across the income distribution and more specific concerns relating to inter-generational outcomes. In Ireland in 2008 there was a clear age gradient in relation to economic stress. Over time the gradient became sharper with the relative position of younger groups deteriorating. The increased salience of age group differentiation in Ireland involved two components. The first related to variability in increases in stress across the age spectrum that was common across income class categories. In that respect children and the older middle age group suffered most. The second involves changes in the additional effects of poverty. While the variable impact of poverty increased the differentials between the elderly and all other groups, it reduced the degree of differentiation between the non-elderly groups. It is not possible to understand the impact of the Great Recession in Ireland by focusing only on changing relativities in relation to social class, unless one allows for the fact that the changing impact of life course stage varied across income classes and the scale of absolute increases in economic stress levels for the non-elderly groups experienced across all income classes. That the Irish pattern of change was not an inevitable outcome of the economic crisis is illustrated by the fact that in Iceland a similar starting point produced a quite different set of changes. Greece, on the other hand, provides an example of the emergence of significant age related differentiation where the pre-recession period was characterised by their absence. Clearly policy choices not only affect life course differentiation but the extent to which operates in a uniform or variable fashion across income classes.